A Robotic Irrigation System: motivating basic school students to science - Esteves, Zita (2012)
The active involvement of our students, from early ages, in the study of science requires a constant motivational effort. Robotics is an actual subject rather appealing to our youngsters. On the other hand interdisciplinary approaches are possible in different science subjects using robots or robotics systems or concepts. In the frames of the 2nd Portuguese “Hands-on Science” science fair a group of basic school students was suggested to develop a science fair project using a robotic kit. In this communication we will present our approach and how the students developed their activities and the results achieved. The student’s motivation to work by themselves on their spare time, their enthusiasm, commitment, success and also the difficulties faced are analyzed. We will show that projects such as this one allow the positive involvement and interaction of students with science. Even heterogeneous groups can work successfully with this kind science fair projects.